Mini-Review on Capacity-Building for Data-Driven Early Childhood Systems: The Consortium for Pre-primary Data and Measurement in Sub-Saharan Africa - Raikes, Abbie; Sayre, Rebecca; Davis, Dawn (Frontiers in Public Health, 2021)
Low- and middle-income countries (LMIC) are increasing investments in early childhood development programs, including early childhood education. As programs reach scale, there is increasing demand for evidence on impacts of investments. Little work to date has examined capacity required to effectively use data at scale in LMIC, including opportunities and barriers to integrating data into ongoing program implementation and tracking child development and quality of services at scale. Below we outline the rationale and approach of the Consortium for Preprimary Data & Measurement in sub-Saharan Africa, focused on building capacity for data-driven decision-making in early childhood systems. Themes from the first phase include the importance of building diverse groups of stakeholders to define priorities for data and measurement; the need for coordinated and strategic investments in data and measurement; and the value of long-term investments in government/civil society/university partnerships to generate locally-relevant data on early childhood.